2017
DOI: 10.1007/s00404-017-4458-x
|View full text |Cite
|
Sign up to set email alerts
|

What can we do to reduce the associated costs in induction of labour of intrauterine growth restriction foetuses at term? A cost-analysis study

Abstract: Misoprostol for induction of labour had lower related costs than dinoprostone or Cook balloon, with similar obstetrical and perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…The induction-to-birth interval was significantly shorter and the proportion of vaginal deliveries within 24 h was higher in the Propess group than in the Prostin E2 group. The success rates were higher (90% and 96.7% in the Prostin and Propess groups, respectively) than those in many other previous studies, with a success rate ranging from 71% to 90.4% [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. We assumed that the efficacy of Propess would be better than that of Prostin E2 tablets in IOL.…”
Section: Discussioncontrasting
confidence: 61%
“…The induction-to-birth interval was significantly shorter and the proportion of vaginal deliveries within 24 h was higher in the Propess group than in the Prostin E2 group. The success rates were higher (90% and 96.7% in the Prostin and Propess groups, respectively) than those in many other previous studies, with a success rate ranging from 71% to 90.4% [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. We assumed that the efficacy of Propess would be better than that of Prostin E2 tablets in IOL.…”
Section: Discussioncontrasting
confidence: 61%
“…Disadvantages of COOK balloons include the possibility of potential infections, premature rupture of membranes, and cervical damage (13). Duro-Gómez reported the cost of misoprostol for IOL was lower than that of dinoprostone or COOK balloons, with similar obstetric and perinatal outcomes (15). Fan et.al reported that the success rate of COOK balloons for cervical ripening (100%) was signi cantly higher than that of oxytocin (79.38%), and the vaginal delivery rate was signi cantly higher in the balloon group (81.25% vs. 65%, P < 0.05) as well.…”
Section: Discussionmentioning
confidence: 97%
“…Bishop score ≥ 6 indicates mature cervix, with a higher score indicating higher success rate of IOL (13). Bishop score < 6 indicates immature cervical that requires cervical maturation promotion (13) (15). In contrast, the risk of hyper-stimulation of mechanical methods is lower than that of PGE, while the risks of CS and infection are similar (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is not a harmless technique and for this reason it is important to have adequate protocols in order to optimize resources and diminish risks. 2 In this review, we present the main controversies related to IOL.…”
Section: Introductionmentioning
confidence: 99%